Income Analysis Of Fisherman Family In Village Kerasian Island, Laut Island District Kotabaru District Islands South Kalimantan Province - Mutia Wahda (Income Journal Of Economics Development, 2021)
This study aims to analyze the income of fishermen's families, and find out the sources of income for fishermen's families in Pulau Kerasian Village, Pulau Laut Islands, Kotabaru Regency, South Kalimantan Province. This study used descriptive qualitative method. Data collection is done by observation, interviews and documentation. In this study the data sources used in data collection include primary data and secondary data. The analysis technique used is income analysis which includes cost analysis, fisherman income analysis, profit analysis, non-fisherman income analysis, fisherman family income analysis. The results showed that the income of the fishermen's family was Rp. 6,687,540 categorized as very high income. The high income is because some family members have jobs so that they help increase family income, the high income is also due to the fishermen's family spending a little compared to their income. Other sources of income for fishermen's families are carpenters, construction workers, traders, gardeners, entrepreneurs, farm laborers, and temporary employees and others. The other sources of income are carried out by the head of the family and family members such as the fishermen's wives and children as well as the fishermen themselves